MAJAPAHIT DALAM LINTAS PELAYARAN DAN PERDAGANGAN NUSANTARA - Bambang Budi Utomo (Berkala Arkeologi, 2009)
Majapahit has been known as agrarian and maritime kingdom as well, with a territory covered almost as wide as the nowadays Republic of Indonesia region, excluding part of Papua and West Java (the Sundanese Kingdom). This was the condition after Gajah Mada well-known vow, the Palapa. Long before Mahāpatih Gajah Mada spoke his vow, from the year 1292 CE inscription of Camundi one’s learned that the consecration of the statue of Bhattari Camundi during the time of Śrī Mahārāja Kěrtanāgara from Siŋhasāri was a token of his success in bringing all the areas and many islands around under his power. And that means that the idea of expanding the Java mandala had been managed by Śrī Mahārāja Kěrtanāgara since the 1270-s before the inscription of Camundi was established. Based on available written sources (scripts and inscriptions) and being compared to Siŋhasāri maṇḍala expansion, regions that were under Majapahit’s authority covered only parts of Central Java, East Java, Madura, Bali and Sumbawa. Majapahit’s power was very depended on the services of the coastal ports such as Kambangputih, Siddhayu, Gresik, Surabhaya, and Canggu. And as to it Majapahit established powerful navy arms to secure the Majapahit waters in the Java Sea. The Babad Lasĕm mentioned Lasĕm to be the port where Rājasawarddhana (Bhre Matahun) warships anchored. Rājasawarddhana was the ruler of Lasĕm who happened to be Hayam Wuruk’s relatives. All these warships were assumed to protect Majapahit’s waters in the Java Sea.